A practical handbook of preparative HPLC - Wellings, Donald A.
This book is a distillation of twenty years of practical experience of the high pressure liquid chromatography (HPLC) process. Deliberately steering clear of complex theoretical aspects, this book concentrates on the everyday problems associated with the technique, making it perfect for frequent use in the laboratory and for those in the pharmaceutical, agrochemical and biotechnology industries for the analysis and purification of drugs, small molecules, proteins and DNA. This book Provides practical, hands-on advice based on years of experience Will help ensure optimal design, equipment and separation results for your particular task Presents system layouts from laboratory to process scale Will help you to devise or improve record-keeping and documentation systems Provides practical, hands-on advice based on years of experience Will help ensure optimal design, equipment and separation results for your particular task Presents system layouts from laboratory to process scale Will help you to devise or improve record-keeping and documentation systems.